Dayung Borih, The Conduits Of The Bidayuh And The Spiritual World - Yvonne Michelle, Campbell; Damien, Mikeng (the Department of Southeast Asian Studies, University of Malaya, 2019)
Dayung Borih, or Bidayuh priestess and Gawai are two important cultural elements within the context of the traditional Bidayuh of Sarawak. This paper examines the role and significance of Gawai and Dayung Borih within the Bidayuh community. The data for this study was collected through a series of interviews and participant observations conducted in two villages in the Bau district. The interviews revealed that the concept of Gawai in the olden days was a form of rituals relating human to spiritual beings with the help of the Dayung Borih acting as mediators. The role of Dayung Borih was not only limited to mediators but also healers whereby they performed healing Gawai. The traditional Bidayuh believed that these Dayung Borih were gifted women selected by the spirits themselves. It was a highly respected position within the Bidayuh community but physically, mentally and spiritually demanding for these women. However, the number of Dayung Borih is decreasing and together with it their significant in the community as well as the concept of Gawai, which has changed due to modernisation within the Bidayuh community.